Risk Factors for Healthcare-Associated Infections After Pediatric Cardiac Surgery*. Issue 3 (March 2018) - Hatachi, Takeshi; Tachibana, Kazuya; Inata, Yu; Tominaga, Yuji; Hirano, Aiko; Kyogoku, Miyako; Moon, Kazue; Shimizu, Yoshiyuki; Isaka, Kanako; Takeuchi, Muneyuki
Abstract : Objectives: Healthcare-associated infections after pediatric cardiac surgery are significant causes of morbidity and mortality. We aimed to identify the risk factors for the occurrence of healthcare-associated infections after pediatric cardiac surgery. Design: Retrospective, single-center observational study. Setting: PICU at a tertiary children's hospital. Patients: Consecutive pediatric patients less than or equal to 18 years old admitted to the PICU after cardiac surgery, between January 2013 and December 2015. Interventions: None. Measurements and Main Results: All the data were retrospectively collected from the medical records of patients. We assessed the first surgery during a single PICU stay and identified four common healthcare-associated infections, including bloodstream infection, surgical site infection, pneumonia, and urinary tract infection, according to the definitions of the Centers for Disease Control and Prevention and National Healthcare Safety Network. We assessed the pre-, intra-, and early postoperative potential risk factors for these healthcare-associated infections via multivariable analysis. In total, 526 cardiac surgeries (394 patients) were included. We identified 81 cases of healthcare-associated infections, including, bloodstream infections ( n = 30), surgical site infections ( n = 30), urinary tract infections ( n = 13), and pneumonia ( n = 8). In the case of 71 of the surgeries (13.5%), at least one healthcare-associated infection was reported. Multivariable analysis indicated the following risk factors for postoperative healthcare-associated infections: mechanical ventilation greater than or equal to 3 days (odds ratio, 4.81; 95% CI, 1.89–12.8), dopamine use (odds ratio, 3.87; 95% CI, 1.53–10.3), genetic abnormality (odds ratio, 2.53; 95% CI, 1.17–5.45), and delayed sternal closure (odds ratio, 3.78; 95% CI, 1.16–12.8). Conclusions: Mechanical ventilation greater than or equal to 3 days, dopamine use, genetic abnormality, and delayed sternal closure were associated with healthcare-associated infections after pediatric cardiac surgery. Since the use of dopamine is an easily modifiable risk factor, and may serve as a potential target to reduce healthcare-associated infections, further studies are needed to establish whether dopamine negatively impacts the development of healthcare-associated infections.